Timing of Sleep and Its Relationship with the Endogenous Melatonin Rhythm - Sletten, Tracey L.; Vincenzi, Simon; Redman, Jennifer R.; Lockley, Steven W.; Rajaratnam, Shantha M. (Frontiers in Neurology, 2010)
While much research has investigated the effects of exogenous melatonin on sleep, less is known about the relationship between the timing of the endogenous melatonin rhythm and the sleep-wake cycle. Significant inter-individual variability in the phase relationship between sleep and melatonin rhythms has been reported although the extent to which the variability reflects intrinsic and/or environmental differences is unknown. We examined the effects of different sleeping schedules on the time of dim light melatonin onset (DLMO) in 28 young, healthy adults. Participants chose to maintain either an early (22:30 – 06:30 h) or a late (00:30 – 08:30 h) sleep schedule for at least three weeks prior to an overnight laboratory visit. Saliva samples were collected under dim light (<2 lux) and controlled posture conditions to determine salivary DLMO. The 2 hour difference between groups in the enforced sleep-wake schedule was associated with a concomitant 1.75 hour delay in DLMO. The mean phase relationship between sleep onset and DLMO remained constant (~2 hours). The variance in DLMO time, however, was greater in the late group (range 4.5 hours) compared to the early group (range 2.4 hours) perhaps due to greater effect of environmental influences in delayed sleep types or greater intrinsic instability in their circadian system. The findings contribute to our understanding of individual differences in the human circadian clock and have important implications for the diagnosis and treatment of circadian rhythm sleep disorders, in particular if a greater normative range for phase angle of entrainment occurs in individuals with later sleep-wake schedules.